Review of oil–water through pipes. (October 2015) - Ismail, Ahmad Shamsul Izwan; Ismail, Issham; Zoveidavianpoor, Mansoor; Mohsin, Rahmat; Piroozian, Ali; Misnan, Mohd Shahir; Sariman, Mior Zaiga
Abstract: In oilfield operations, co-current flow of oil–water mixture is very common and can cause significant flow assurance problems during production. Accurate knowledge of behaviour of oil–water in a pipeline flow is crucial to design/optimize production, transportation, and processing facilities. Many researchers have attempted to generalize the liquid–liquid or the two phase flow systems through mechanical models and develop means for predicting the flow patterns, pressure drop, and water holdups. However, the crude oil properties differ and the oil–water system can be operated over various range of operating conditions and subsequently encounter an altered hydrodynamics behaviour in two phase flow system. To worsen the situation, almost all the empirical correlations and mechanical models developed were for low viscosity oil and with majority focused on gas–liquid flow. Thus, comprehensive models still remain unsolved for some of the flow issues especially when involving high viscosity or waxy crude oils. Hence an attempt to generalize liquid–liquid flow in multiphase systems seems impractical. Since conventional light crude oil or easy oil reserves are gradually depleted, thus many research works on high viscosity oil–water flow in pipes have been initiated. Presently, there is limited number of papers on high viscous oil–water flow in open literature which has confined the understanding of the flow behaviour of two-phase flow. In this communication, we report a review on the current state of research on two phase flow oil–water phenomena, highlighting what is so far has been realized and how this knowledge can be applied as a basis to understand better of the more complex cases of gas-crude oil–water three phase flow. Highlights: The review discusses the past, present, and future trends of two phase flow in pipes. Critically reviewed the gaps and limitations of published works that could contribute to future works in two phase flow. A thorough discussion on the oil–water characteristics as well as mechanisms involved in studying the two phase flow phenomena.